Amino acids based on metabolic therapy in epileptic dogs. Organisms’ compensatory ability as the reason of limited clinical efficacy - Цвіліховський, М. І.; Якимчук, О. М.; Іванченко, Н. Ю. (Scientific Progress & Innovations, 2018)
The epilepsy is the most widespread chronic neurological disorders among animals, as well as among people. According to scientific literature such amino acids, as leucine, isoleucine, valine, glycine and taurine appears to be promising regarding antiepileptic effect. The aim of our investigation was to estimate the ability of amino acid mixture to prevent epileptic seizures in dogs and to analyze changes that take place in the blood amino acid pool of this species in case of exogenous amino acid overload. Eight dogs of different breeds with which were diagnosed as such that had probably symptomatic epilepsy («unknown cause epilepsy», IVETF) were engaged in the experiment. During 2 months of the experiment the dogs received amino acids orally in such daily doses per kilogram divided equally in order to be given every 8 hour: L-leucine – 150 mg, L-isoleucine – 275 mg; L- valine – 240 mg; glycine – 300 mg; taurine – 240 mg. The efficacy was estimated by visual detection of paroxysmal activity and quantitative electroencephalography using fast Fourier transformation to the frequency range of bands corresponding 0.5–3.0 Hz for delta, 4.0–7.0 Hz for theta, 8.0–13.0 Hz for alpha and β 14.0–40.0 Hz for beta bands. The detection of the concentration of amino acids in serum and cerebrospinal fluid was performed by ion exchange liquid chromatography. Sick dogs demonstrated higher frequency ranges of delta, theta and alpha bands and lower frequency range of beta band comparing to healthy dogs. After one-month treatment the frequency ranges of delta, theta and alpha bands lowered whereas the frequency of beta band became higher. Clinically antiepileptic effect of amino acid composition was represented by the prolongation of interictal periods per 2 to 3 times. After one month treatment the amount of BCAA in serum increased as well as the amount of other amino acids. Also the molar ratio of serum acids was changed. The concentration of such amino acids as leucine, glycine, taurine and serine in cerebrospinal fluid was increased. After the second month of treatment the tendency to serum amino acid ratio stabilization was noticed. The period of efficacy was short (approximately 35–48 days). To our opinion it is due to compensatory mechanisms of protein metabolism that were represented by partial amino acid molar ratio stabilization. The complex of L-leucine, L-isoleucine, L-valine, glycine and taurine possesses the anticonvulsant activity in 37,5 % of cases when being given orally to dogs with probably symptomatic epilepsy. The brief period of efficacy of such metabolic therapy is due to compensatory processes which take place in dogs’ organisms. Further investigations regarding amino acids’ anticonvulsant properties in dogs seam to be perspective and should be carried out.